Why the West recognise poet-philosopher Muhammad Iqbal - Hasan, Md. Mahmudul (New Straits Times Press, 2023)
A believer in the oneness of God and deeply immersed in Islam, Iqbal was a "modernist who argued in favour of going directly to sacred scripture" and "turned away from much of what was labelled 'the West', denouncing the nationalism, militarism and imperialism that the Great War had thrown into high relief" (Metcalf). Iqbal's critical stance against the ideological and hegemonic forces of Europe didn't prevent him from being recognised by the West. In 1922, the British government decided to honour him with knighthood. Citing the case of Iqbal's wider appreciation in the West, I tell my students that in order to get recognition in this world, they need self-worth and sound academic rigour – not adaptation and capitulation to foreign cultural values.